Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3* The Natural Exponential Function - 6.3* Exercises - Page 453: 62



Work Step by Step

$f(x)=xe^{-x}$ $f'(x)=\frac{d}{dx}xe^{-x}$ $f'(x)=e^{-x}\frac{d}{dx}(x)+x\frac{d}{dx}(e^{-x})$ $f'(x)=e^{-x}-x(e^{-x})$ Again differentiate with rest to x, we get $f''(x)=-2e^{-x}+x(e^{-x})$ Take third derivative of the function. $f'''(x)=3e^{-x}-x(e^{-x})$ Proceeding this process in the same way up to nth derivative, we observe the expression for nth derivative can be calculated as follows: $f^{n}(x)=(-1)^{(n-1)}(ne^{-x})+(-1)^{n}(xe^{-x})$ Take n = 1000, therefore, $f^{1000}(x)=(-1)^{(1000-1)}(1000e^{-x})+(-1)^{1000}(xe^{-x})$ $f^{1000}(x)=(-1)^{(999)}(1000e^{-x})+(-1)^{1000}(xe^{-x})$ Hence, $f^{1000}(x)=-1000e^{-x}+xe^{-x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.